Switching Adolescent High-Fat Diet to Adult Control Diet Restores Neurocognitive Alterations - Boitard, Chloé; Parkes, Shauna L.; Cavaroc, Amandine; Tantot, Frédéric; Castanon, Nathalie; Layé, Sophie; Tronel, Sophie; Pacheco-Lopez, Gustavo; Coutureau, Etienne; Ferreira, Guillaume (Frontiers in Behavioral Neuroscience, 2016)
In addition to metabolic and cardiovascular disorders, obesity is associated with adverse cognitive and emotional outcomes. Its growing prevalence in adolescents is particularly alarming since this is a period of ongoing maturation for brain structures (including the hippocampus and amygdala) and for the hypothalamic-pituitary-adrenal (HPA) stress axis, which is required for cognitive and emotional processing. We recently demonstrated that adolescent, but not adult, high-fat diet (HF) exposure leads to impaired hippocampal function and enhanced amygdala function through HPA axis alteration (Boitard et al., 2014; Boitard et al., 2012; Boitard et al., 2015). Here, we assessed whether the effects of adolescent HF consumption on brain function are permanent or reversible. After adolescent exposure to HF, switching to a standard chow diet restored levels of hippocampal neurogenesis and normalized enhanced HPA axis reactivity, amygdala activity and avoidance memory. Therefore, while the adolescent period is highly vulnerable to the deleterious effects of diet-induced obesity, adult exposure to a standard diet appears sufficient to reverse alterations of brain function.